2020
DOI: 10.3390/ijerph17062095
|View full text |Cite
|
Sign up to set email alerts
|

The Daily Mile Is Able to Improve Cardiorespiratory Fitness When Practiced Three Times a Week

Abstract: The Daily Mile is a promising initiative aimed at removing some of the barriers to physical activity in the school setting. This quasi-experimental study investigated the dose–effect of The Daily Mile on cardiorespiratory fitness, waist-to-height ratio, and body mass index (BMI) after a period of 3- and 6-months. A total of 279 students (mean age = 9 ± 1 years) participated in The Daily Mile while 269 students (mean age = 9 ± 1 years) did not (control group). A posteriori, the classes performing The Daily Mile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 27 publications
0
49
0
Order By: Relevance
“…If they responded positively, they were asked the name of the programme, how long they had been participating, and how often their class took part. The core principles of the Daily Mile™ are that participants should take part on at least 3 days of the week and while there is variability reported in schools approach to undertaking this (e.g., Ryde et al, 2018 ), we used this criteria to clarify participation in line with Brustio et al (2020) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…If they responded positively, they were asked the name of the programme, how long they had been participating, and how often their class took part. The core principles of the Daily Mile™ are that participants should take part on at least 3 days of the week and while there is variability reported in schools approach to undertaking this (e.g., Ryde et al, 2018 ), we used this criteria to clarify participation in line with Brustio et al (2020) .…”
Section: Methodsmentioning
confidence: 99%
“…In a quasi-experimental pilot study conducted over 8 months with 391 pupils, The Daily Mile™ was found to lead to increases in moderate-to-vigorous physical activity (MVPA) and fitness, reduction in time spent being sedentary, and improvements in body composition ( Chesham et al, 2018 ). Following this, several studies have examined the impact of The Daily Mile™ on fitness after 3–6 months ( Brustio et al, 2019 , 2020 ; de Jonge et al, 2020 ). To our knowledge, no longer term examination of the impact on pupil fitness has been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, cardiorespiratory endurance has also been characterized as a strong health marker, as increased cardiorespiratory endurance is associated with healthier bodyweight and waist circumference [ 27 ]. Several different national (e.g., in Germany [ 28 ], Slovenia [ 29 ], the USA [ 30 ], Australia and Finland [ 31 ], and South Africa [ 32 ]) and international (e.g., the “Daily Mile” project ( , 5 March 2022) [ 33 , 34 , 35 , 36 ]) interventions have been implemented to increase public awareness, with outcomes showing a trend reversal in physical fitness levels [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies evidenced that MVPA (moderate to vigorous physical activity) is strongly associated with motor performances, and inversely related to adiposity (Júdice et al, 2017;Santos et al, 2019;Jones et al, 2020). Interventions aimed at improvement of resistance and cardiorespiratory fitness in youth and adolescents are often based on the amount of daily/weekly physical activity (3 -5 times a week), and the evolution in motor performances is dose-effect dependent (Brustio et al, 2020;Martin-Smith et al, 2020;Nevill et al, 2020).…”
Section: Discussionmentioning
confidence: 99%